α-Cluster formation in heavy α-emitters within a multistep model - J.M. Dong; Q. Zhao; L.J. Wang; W. Zuo; J.Z. Gu (Physics Letters B, 2021)
α-decay always has enormous impetuses to the development of physics and chemistry, in particular due to its indispensable role in the research of new elements. Although it has been observed in laboratories for more than a century, it remains a difficult problem to calculate accurately the formation probability Sα microscopically. To this end, we establish a new model, i.e., multistep model, and the corresponding formation probability Sα values of some typical α-emitters are calculated without adjustable parameters. The experimental half-lives, in particular their irregular behavior around a shell closure, are remarkably well reproduced by half-life laws combined with these Sα. In our strategy, the cluster formation is a gradual process in heavy nuclei, different from the situation that cluster pre-exists in light nuclei. The present study may pave the way to a fully understanding of α-decay from the perspective of nuclear structure.